Comparison of ProSeal laryngeal mask airway, classical laryngeal mask airway with endotracheal tube in gynecological laparoscopy under controlled ventilation - Patel, Anupkumar S.; Jain, Namrata (International Journal of Advances in Medicine, 2019)
Background: PLMA is a recent, complex, and ingenious development with some added feature of classic LMA like modified dual cuff, drain tube, positive pressure ventilation at higher peak inspiratory pressure. Study was to evaluate and compare the use of classical laryngeal mask airway, ProSeal laryngeal mask airway, and endotracheal tube with controlled ventilation in patients undergoing gynecological laparoscopic procedure. Methods: About 150 patients, ASA risk I and II, posted for elective gynecological laparoscopy were recruited in the study. All the patients between 18 to 45years of age were randomly divided in three groups, group PLMA, group CLMA, group ETT (50 patients each). Attempt of insertion of airway device, leaks pressure, pulmonary ventilation, hemodynamic; heart and MAP, gastric distention was recorded. All patients were of middle age group, comparable in weight. Mean duration of laparoscopy was comparable in all the groups. Results: Significant rise in heart rate and mean arterial pressure seen in group ETT after induction of anesthesia. Changes in the end tidal CO2 and peak airway pressure after induction of anesthesia, before and after pneumoperitonium were comparable in all three groups. After head low position peak airway pressure is slightly raised in group PLMA, group CLMA. Gastric distension was noted higher in group 10 % as compare to group PLMA (8%) and group (2%). Incidence of sore throat (22%), nausea vomiting (14%) and airway trauma (14%) was higher in group ETT. Conclusions: Hemodynamic stability was better in and CLMA group at time of induction and comparable in all three groups at time of pneumoperitoneum and trendelenburg position along with pulmonary ventilation. Post-operative sore throat, nausea vomiting was higher with endotracheal tube.